Proliferation and apoptosis of lymphocytes in response to borrelia antigen stimulation in Lyme-borreliosis patients - Ye. N. Ilyinskikh; I. N. Ilyinskikh; A. G. Semyonov; Ye. A. Fait; M. V. Shaitarova (Бюллетень сибирской медицины)
The object of this work was to study the correlation between the lymphocyte proliferation and apoptosis in the cultures stimulated by specific inactivated Borrelia garinii antigen and the different clinical outcomes in Lyme borreliosis patients. It was found that borrelia antigen stimulation of the cultures obtained from chronic patients induced T helper type 1-like response as well as depression in lymphocyte apoptosis, which may provide the basis of persistent activated T cell immune response and chronic inflammatory in Lyme borreliosis.